NHS funding, resources and treatment volumes - Max Warner; Ben Zaranko (Institute for Fiscal Studies (IFS), 2022)
Last month, the Chancellor set out additional funding for the National Health Service (NHS) in the Autumn Statement. This came alongside the promise of new recovery plans and targets for emergency care and primary care, a recommitment to the elective recovery plan, and a promise of a comprehensive workforce plan. These announcements come against a backdrop of continued operational pressure on all parts of the NHS, and high inflation putting pressure on NHS budgets and staff pay. In this report, the second part of the three-part series, we dig deeper into the resources available to the NHS and how they are being used, looking beyond just the waiting list. We first examine how the funding, staffing and hospital beds available to the NHS have changed since 2019. We then show how the number of patients treated by the NHS in eight different areas compares with 2019 levels. For most areas of care, the NHS is still struggling to treat more people than it was pre-pandemic, despite having - on the face of it - additional staff and funding. We therefore go on to consider a range of different factors that could explain this seeming fall in performance and output.
Keywords: 330; Government finances and spending; Health and social care; NHS waiting lists; COVID-19; Government spending; Healthcare; NHS; Productivity; Public sector